Experimental Study of Acceleration Effect To Hydram Pump Performance - Adhi Suryawan, A.A.; Suarda, Made (Jurnal Energi Dan Manufaktur, 2012)
The hydram pump is a motorless pump, which is its working mechanism use potential energy only. The hydram pump consists of a component called an air vessel. Until now, it is not exactly known yet what is the effect of air vessel to performance of hydram pump. To get the effect of air vessel to performance of hydram pump can be used indicator diagram. This research carried out by use of head and the length variation of drive pipe of the hydram pump. Then, characteristic in drive pipe and delivery pipe of the hydram pump were observed. The results show that the use of the air vessel in the hydram pump able to decrease the acceleration head significantly which happened in delivery pipe, that is 0,35 meters to 0,04 meters, so that the pumped water to the reservoir through delivery pipe is more stable. In addition, the efficiency increase from 17,03% up to 52,99%. So, the air vessel gives a big effect to the performance of hydram pump.
Keywords: Indicator diagram, Air vessel, Acceleration Head, Hydram pump.